Systematic review and meta-analysis of residential radon and lung cancer in never-smokers. (3rd February 2021) - Cheng, Elvin S.; Egger, Sam; Hughes, Suzanne; Weber, Marianne; Steinberg, Julia; Rahman, Bayzidur; Worth, Heather; Ruano-Ravina, Alberto; Rawstorne, Patrick; Yu, Xue Qin
Background: Globally, radon is the leading risk factor for lung cancer in never-smokers (LCINS). In this study, we systematically reviewed and meta-analysed the evidence of the risk of LCINS associated with residential radon exposure. Methods: Medline and Embase databases were searched using predefined inclusion and exclusion criteria to identify relevant studies published from 1 January 1990 to 5 March 2020 focused on never-smokers. We identified four pooled collaborative studies (incorporating data from 24 case–control studies), one case–control study and one cohort study for systematic review. Meta-analysis was performed on the results of the four pooled studies due to different measures of effect and outcome reported in the cohort study and insufficient information reported for the case–control study. In a post hoc analysis, the corresponding risk for ever-smokers was also examined. Results: Risk estimates of lung cancer from residential radon exposure were pooled in the meta-analysis for 2341 never-smoker cases, 8967 never-smoker controls, 9937 ever-smoker cases and 12 463 ever-smoker controls. Adjusted excess relative risks (aERRs) per 100 Bq·m −3 of radon level were 0.15 (95% CI 0.06–0.25) for never-smokers and 0.09 (95% CI 0.03–0.16) for ever-smokers, and the difference between them was statistically insignificant (p=0.32). The aERR per 100 Bq·m −3 was higher for men (0.46; 95% CI 0.15–0.76) than for women (0.09; 95% CI −0.02–0.20) among never-smokers (p=0.027). Conclusion: This study provided quantified risk estimates for lung cancer from residential radon exposure among both never-smokers and ever-smokers. Among never-smokers in radon-prone areas, men were at higher risk of lung cancer than women. Globally, radon is the leading cause of lung cancer in never-smokers. Yet its quantified link with lung cancer risk among never-smokers is not known. This study computes the risk estimate of lung cancer from residential radon exposure among never-smokers. https://bit.ly/32frCbq